A Divergence in the Peninsula: Why has North Korea Developed Nuclear Weapons, Yet South Korea Has Refrained? Predicting Iran's Nuclear Future Using a Comparative Case Study - Heverin, Kathleen (Colloquium: The Political Science Journal of Boston College, 2025)
This paper analyzes the conditions under which states develop nuclear weapons. North and South Korea present cases of similarly situated states going in opposite directions concerning nuclear weapons development. By analyzing the climactic movements in North and South Korean history of nuclear weapons development, I have determined that states need two necessary conditions to develop nuclear weapons: motivation and means. States are motivated by a security concern. When this is coupled with means in the form of state capability, either from sufficient domestic economic advancement or foreign aid, nuclear weapons development occurs. This issue has modern policy implications in security and regional stability. In the case of Iran, nuclear weapons development is likely, as both conditions of security concern, and state capability are present. Identifying these conditions can help determine how to shape policies to prevent nuclear proliferation and restrict a regime that is widely considered unstable from gaining this type of potential for destruction.